Skeletal deformities in larval and juvenile stages of cultured white seabream Diplodus sargus and common two-banded seabream Diplodus vulgaris - Nicolau, L. (2014)
Species diversification is presently a major concern amongst aquaculture researchers and producers trying to find new profitable species for commercial production and restocking. White seabream Diplodus sargus (Linnaeus, 1758) and common two-banded seabream Diplodus vulgaris (Saint-Hillaire, 1817) are two new promising sparid species for aquaculture production, as an alternative to gilthead seabream Sparus aurata and sea bass Dicenthrarchus labrax, since they present different spawning seasons and good growth ratios.